Sonographic Gallbladder Abnormality Is Associated with Intravenous Immunoglobulin Resistance in Kawasaki Disease - Chih-Jen Chen; Fu-Chen Huang; Mao-Meng Tiao; Ying-Hsien Huang; Li-Yan Lin; Hong-Ren Yu; Kuender D. Yang; Yi-Chuan Huang; Chih-Cheng Chen; Wei-Chiao Chang; Ho-Chang Kuo (The Scientific World Journal)
Objective. Kawasaki disease (KD) is an acute systematic vasculitis in children which causes coronary arterial lesions and hydrops of gallbladder. Our objective is to correlate the clinical significance and influence on disease outcome of patients with gallbladder abnormalities in Kawasaki dissease. Methods. Children who met KD diagnosis criteria and were admitted for IVIG treatment were retrospectively enrolled for analysis. Patients with abdominal sonography were divided into 2 groups based on the absence (Group A, N=61) or presence (Group B, N=16) of gallbladder abnormalities (GBA), defined as hydrops or acalculous cholecystitis. Between the two groups, clinical features, demographic data (including admission days, coronary artery lesions, IVIG resistance), and laboratory data before/after IVIG treatment were collected for analysis. Results. The presence of sonographic gallbladder abnormalities is correlated with higher levels of serum CRP, GPT, and neutrophils. It also points to an increased number of IVIG resistance rates in group B. There was no significant statistical difference among clinical features, age, gender, admission days, or coronary artery lesions between the two groups. Conclusion. Sonographic gallbladder abnormalities are associated with higher CRP, GPT, neutrophil and IVIG resistance in KD. It can be used as a predictor of IVIG resistance in patients with KD.